Navigating the unknown: Uncertainty moderates the link between visionary leadership, perceived meaningfulness, and turnover intentions - Martin Buss; Eric Kearney (Journal of Occupational and Organizational Psychology, 2024)
Visionary leadership is considered to be one of the most important elements of effective leadership. Among other things, it is related to followers' perceived meaningfulness of their work. However, little is known about whether uncertainty in the workplace affects visionary leadership's effects. Given that uncertainty is rising in many, if not most, workplaces, it is vital to understand whether this development influences the extent to which visionary leadership is associated with followers' perceived meaningfulness. In a two-source, lagged design field study of 258 leader-follower dyads from different settings, we show that uncertainty moderates the relation between visionary leadership and followers' perceived meaningfulness such that this relation is more strongly positive when uncertainty is high, rather than low. Moreover, we show that with increasing uncertainty, visionary leadership is more negatively related to followers' turnover intentions via perceived meaningfulness. This research broadens our understanding of how visionary leadership may be a particularly potent tool in times of increasing uncertainty.
Keywords: 650; follower turnover intentions; perceived meaningfulness; uncertainty; visionary leadership